Long-term viscoelastic behavior and evolution of the Schapery model for mirror epoxy - Dardouri Mohsen; Fellah Ali; Gmir Fethi; Aloui Abdessattar (Journal of the Mechanical Behavior of Materials)
Mirror epoxy, used in its pure form with a resin-to-hardener ratio of 100:50, is emerging as an innovative material widely used in modern flooring. Its appeal lies in its smooth, shiny surface, offering a unique and contemporary aesthetic. However, understanding its long-term viscoelastic behavior is essential to ensure the durability and performance of floor coverings under various conditions of use. This study examines the evolution of the Schapery model for mirror epoxy, focusing on its long-term viscoelastic behavior. Creep tests at constant loads and ambient temperature are carried out in order to numerically determine the static nonlinearity factors g and g 0 formulated in the Schapery model. To validate this model, other relaxation tests at constant deformations are carried out under the same conditions, which allowed us to determine the nonlinearity factors h and h 0 formulated in this model using the same method. A remarkable consistency between the variations in the experimental and numerical values of the model programmed on MATLAB allows us to conclude that the Schapery model describes the real behavior of the mirror epoxy in a satisfactory manner.